18F-FDG PET/CT in Infective Endocarditis on Papillary Muscles: A Case Report. (June 2021) - Fang, Na; Zeng, Lei; Jin, Fei; Lin, Shuai; Wang, Yan-li
Abstract : Abstract: Infective endocarditis is a serious, potentially life-threatening condition. The valve leaflets and annulus are the most commonly affected sites, but involvement of the papillary muscles is extremely rare. We present the case of a 69-year-old woman who had infective endocarditis only involving the papillary muscle on 18 F-FDG PET/CT.